2021
DOI: 10.21037/atm-20-8154
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and risk factors for intestinal necrosis in patients with mesenteric ischemia

Abstract: Background: Mesenteric ischemia results in blood flow that is insufficient to meet metabolic demands and subsequent dysfunction of visceral organs, including arterial obstruction and venous thrombosis. Sustained mesenteric ischemia exhausts the ability of capillaries to provide oxygen and initiate an inflammatory reaction, and eventually leads to intestinal mucosal necrosis, a serious and potentially life-threatening condition. Therefore, it is essential that the predictors and risk factors for intestinal necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Mesenteric artery embolism is a severe acute abdominal disease in clinic, characterized by rapid development and high mortality. 11 Early diagnosis is the key to the treatment of mesenteric artery embolism. 12 It has been shown that 13 the mortality of acute intestinal ischemia caused by mesenteric artery embolism is as high as 50%-90%.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric artery embolism is a severe acute abdominal disease in clinic, characterized by rapid development and high mortality. 11 Early diagnosis is the key to the treatment of mesenteric artery embolism. 12 It has been shown that 13 the mortality of acute intestinal ischemia caused by mesenteric artery embolism is as high as 50%-90%.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into context the clinical presentation of the patients, PI and pneumoperitoneum or portal venous gas should not be used as an indication by themselves for an exploratory laparotomy. Additional criteria, including higher C-reactive protein concentrations, higher white blood cell counts, higher lactate levels, and ascites, may be required to indicate inflammatory syndrome and the likelihood of intestinal necrosis from mesenteric ischemia [ 7 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient’s only early sign was fever. Considering that the patient had a history of heart valve replacement and abnormal coagulation function, there was a possibility of thromboembolism, and previous studies have shown that an elevated WBC count is a risk factor for MI progression[ 11 , 12 ]. After excluding blood flow disorders in the lower extremities and heart, MI is one of the complications after major surgery that needs to be considered.…”
Section: Discussionmentioning
confidence: 99%